Upaya Meningkatkan Perkembangan Moral Anak Usia 5-6 Tahun Melalui Metode Bercerita Di TK Swasta Bakti Medan Petisah - Panggabean, Ruth Donda Eleonora; Panni Ance L.Tobing; Murni Lase (Universitas Sari Mutiara Indonesia, 2024)
The purpose of this study was to improve Children Moral Development Aged 5 - 6 Years through Storytelling Method at Bakti Private Kindergarten, Medan Petisah. This research is a Classroom Action Research (CAR) with a quantitative descriptive approach. The subjects of this study were children group B aged 5 - 6 years, totaling 9 children. Data collection techniques used are observation and documentation. Based on the results of the study it was found that there was an increase in children's moral development through the storytelling method of children group B at Bakti Private Kindergarten Medan Petisah in Academic Years of 2022/2023. This can be proven from the moral development of children in the pre-cycle was 27.6%, then in the first cycle was 48.78% and increased to 89.56% in the second cycle. So it can be concluded that the Storytelling Method Improving Children Moral Development Aged 5 - 6 Years in Bakti Private Kindergarten Medan Petisah.